AT2R Autoantibodies Block Angiotensin II and AT1R Autoantibody-Induced Vasoconstriction. Issue 4 (October 2015) - Liles, Campbell; Li, Hongliang; Veitla, Vineet; Liles, Jonathan T.; Murphy, Taylor A.; Cunningham, Madeleine W.; Yu, Xichun; Kem, David C.
<x xml:space="preserve">Abstract</x> Activating autoantibodies to the angiotensin type 1 receptor (AT1R) are associated with hypertensive disorders. The angiotensin type 2 receptor (AT2R) is known to counter-regulate the actions of AT1R. We investigated whether AT2R autoantibodies produced in immunized rabbits will activate AT2R and suppress the vasopressor responses to angiotensin II and AT1R-activating autoantibodies. Five rabbits immunized with a peptide corresponding to the second extracellular loop of AT2R developed high AT2R antibody titers. Rabbit anti-AT2R sera failed to directly dilate isolated rat cremaster arterioles; however, when co-perfused with angiotensin II or AT1R-activating autoantibodies, the anti-AT2R sera significantly inhibited their contractile effects. Rabbit anti-AT2R sera recognized a predominant sequence near the N-terminus of the AT2R second extracellular loop. A decoy peptide based on this sequence effectively reversed the opposing effect of the anti-AT2R sera on angiotensin II–induced contraction of rat cremaster arterioles. A similar blockade of the anti-AT2R sera effect was observed with the AT2R antagonist PD 123319 and the guanylyl cyclase inhibitor 1H-[1, 2, 4]oxadiazolo[4, 3-a]quinoxalin-1-one. Rabbit anti-AT2R sera reacted specifically with AT2R. No cross-reactivity with AT1R was observed. Blood pressure did not change in immunized animals. However, the pressor responses to incremental angiotensin II infusions were blunted in immunized animals. Thirteen subjects with primary aldosteronism demonstrated increased AT2R autoantibody levels compared with normal controls. In conclusion, AT2R autoantibodies produced in immunized rabbits have the ability to activate AT2R and counteract the AT1R-mediated vasoconstriction. These autoantibodies provide useful and selective tools for the study of their roles in blood pressure regulation and possible therapeutic intervention.